Making a case for computer literacy: the German Informatics Society and the emerging field of computer education, late 1960s–early 1990s. - Flury, Carmen; Geiss, Michael (Paedagogica Historica, 2025)
This article examines the historical contribution of the German Informatics Society (GI) to the establishment of computer education in German schools. It highlights the role of societal interests, international developments, public and professional debates, and technological change in the GI's educational policy recommendations. The historical source base consists of conference proceedings, position papers and other publications by key actors within and outside the GI. Methodologically, the article refers to the concept of strategic fields of action. The article shows how the GI's understanding of computer science played an important role in its initial policy recommendations. With increasing computerisation and then the World Wide Web, the GI had to adapt its recommendations to the now more complex situation in Germany and the polyphonic debate.